A computationally efficient implementation of continuum dislocation dynamics: Formulation and application to ultrafine-grained Mg polycrystals. (March 2023) - Luo, Xi; Zaiser, Michael
Abstract: Continuum dislocation dynamics (CDD) represents the evolution of systems of curved and connected dislocation lines in terms of density-like field variables which include the volume density of loops (or 'curvature density') as an additional field. Since dislocation curvature represents a spatial derivative of the underlying discrete dislocation density tensor, the curvature field evolution equation of necessity contains numerically inconvenient higher-order derivatives of the density fields. We propose a simple approximation to express curvature in terms of density fields, and demonstrate its application to a benchmark problem in deformation of Mg polycrystals. Highlights: Dislocation curvature is approximately expressed by density fields. Back stress related to spatial derivatives of dislocation densities is considered. High-efficient FFT based spectral method is used to solve the boundary value problem. This CDD model is a promising tool for high-throughput calculations of polycrystals.